2000
DOI: 10.1007/bf03019671
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant pulmonary edema after intramuscular ketamine

Abstract: Purpose: To report an unusual case of pulmonary edema following intramuscular ketamine administration. Clinical Features: An eight-year-old, healthy girl presented for dressing of first degree burns on dorsum of hand. Ten minutes after administration of 125 mg ketamine im, she developed laboured breathing, cyanosis, and bilateral crepitations and arterial blood gas analysis showed PaO 2 55 mmHg. There was no evidence of upper airway obstruction. On intubating the trachea, pink frothy fluid emerged from the tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…First, several case reports have shown that ketamine is a possible reason for lung edema in patients during intraoperative period [13, 5]. If this effect occurred at the level of the alveolar or distal airway epithelium, then the threshold for developing alveolar edema could be downregulated or the resolution of edema, in which active ion transport plays an important role, might be reduced by ketamine [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, several case reports have shown that ketamine is a possible reason for lung edema in patients during intraoperative period [13, 5]. If this effect occurred at the level of the alveolar or distal airway epithelium, then the threshold for developing alveolar edema could be downregulated or the resolution of edema, in which active ion transport plays an important role, might be reduced by ketamine [8].…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative pulmonary edema has been reported worldwide following intramuscular or intravenous ketamine administration [15]. Pulmonary edema is the abnormal fluid accumulation in the interstitial or alveolar spaces of the lung.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, Pandey et al have reported that intramuscularly injected large-dose ketamine could cause pulmonary artery hypertension and acute pulmonary edema, indicating a potential unfavorable effect of ketamine despite its favorable effect in inhibiting the production of proinflammatory cytokines. 10 This unfavorable effect limits the use of ketamine in liver surgeries such as the OLT, though ketamine may alleviate hypotension induced by the HIR. Anyway, such adverse effect of ketamine is dosedependent.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, ketamine sometimes causes dramatic hemodynamic changes, which may induce serious pulmonary artery hypertension, provoking or aggravating pulmonary edema. 10 In this study, a single small dose of ketamine was given to rabbits before cross-clamping of the IVC and the HPV, changes in systematic hemodynamics and pulmonary proinflammatory cytokines after hepatic reperfusion were observed to evaluate the effect of ketamine preconditioning on hepatic ischemia-reperfusion (HIR) induced acute lung injury.…”
Section: Introductionmentioning
confidence: 99%